Examining the Regional Economic Integration: Analysis of Cross-border Trade among ASEAN, China, and India - Sadia Abbassy; M Luthfi Hameedi; Fajar B Hirawan (Research Synergy Foundation, 2025)
Researchers have studied economic integration since the late 20th century as global markets become interconnected. ASEAN, China, and India are critical political, economic, and infrastructural players, with a growing middle class of over 3.50 billion projected to rise as the fourth-largest economy by 2030. This study examines trade policies, GDP, FDI, proximity, and regional agreements to assess trade flows and economic integration. This study uses a gravity model with panel data regression (1999-2023) to examine regional trade flows. The gravity model estimates the impact of economic size and distance on trade volumes, whereas panel data regression evaluates the relationship between trade policies and economic integration. Data include trade statistics from secondary sources. The finding reveals that economic integration improves trade volume through aligned policies and economic interdependencies. The gravity model highlights that economic size and proximity sustain trade flows, whereas FDI shows a positive correlation, indicating the potential for more profound integration; the trade potential model examines how trade policies and economic size affect intra-regional commerce, a topic rarely studied in the literature. This study calculates trade potential, offering insights for policymakers to improve trade efficiency. Unlike past research that has isolated ASEAN, China, and India, this study provides a comprehensive regional perspective. However, these limitations exclude exchange rates, technology, language, tariffs, and post-2023 applicability.